Implementasi Sistem Pakar untuk Diagnosis Penyakit Lambung Menggunakan Pendekatan Fuzzy Mamdani Berbasis Website - Yansyah, Ilham Roni; Atmaja, Dewi Marini Umi; Hakim, Arif Rahman; Suwaryo, Niko (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to develop a more specific diagnostic approach for various gastric diseases in humans, such as gastritis, peptic ulcers, gastric cancer, gastric tumors or polyps, dyspepsia, gastroesophageal reflux disease (GERD), gastroparesis, and gastroenteritis. This approach seeks to enhance the accuracy of disease identification based on more detailed symptoms. An expert system utilizing the Fuzzy Mamdani method is designed to reduce reliance on internal medicine specialists, enabling patients to gain preliminary insights into the type of gastric disease they may have. This expert system is implemented on a web-based platform, leveraging information technology to integrate large-scale databases, supporting efficiency, accuracy, and relevance to the latest developments in medical science. By analyzing digestive disorder symptoms, the system can provide detailed diagnoses, offer insights into identified symptoms, and recommend appropriate treatment solutions.